Growth, production, and nutrition quality of Crotalaria juncea L and sweet corn planted by intercropping system - A. Rudiarto; . Sumarsono; E. Pangestu (Jurnal Ilmu dan Teknologi Peternakan, 2014)
This study was conducted to evaluate the effect of planting pattern and plant density on the growth, production and nutrient quality of Crotalaria juncea L and sweet corn planted by intercropping system. The data were statistically analyzed using analysis of variance according to completely randomized design in a 3 x 2 factorial arrangement with four replications and tested further if there were differences between treatments. The first factor of plant density was 6, 12, 16 plants/m2, respectively for K1, K2, K3.. The second factor was planting pattern P1: single row and P2: double rows. Implementation of the research was carried out for 3 months. Data collection for Crotalaria juncea L was performed in the second month while data for sweet corn was taken on the third month of the experimental period. Based on the result and discussion , it can be concluded that the two row planting pattern reduced the growth, production and plant nutrition quality of sweet corn, but it promoted growth, production and quality of crop nutrients of Crotalaria juncea L except for the amount of leaves of the Crotalaria juncea L. The density of 6 to 16 plants/m2 decreased growth, production and quality of plant nutrients.